Method for directionally regulating and controlling content of amylose in starch and improving performance of starch film
By using cellulose nanofiber filaments to immobilize the prolanase in the starch film, the problem of insufficient performance of traditional starch films is solved, and the mechanical properties and barrier properties of the starch film are improved.
Patent Information
- Application Number
- CN202411431947.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional starch films have shortcomings in mechanical strength, moisture barrier properties and weather resistance, which limits their promotion in practical applications.
Insolubly dry starch is formed by dissolving the starch in an ionic liquid and drying it in an ozone environment, then immobilizing the Pullanase using cellulose nanofibers to form the Pul@CNF complex, and finally processing in a pressure cooker to prepare the starch film .
It significantly improves the mechanical properties and barrier properties of starch films, improves the stability and enzyme activity of prolulanase, and solves the problem of insufficient performance of traditional starch films.
Smart Images

Figure CN119432946A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of food technology, and in particular to a method for directionally regulating the content of straight chains in starch and improving the performance of starch films. Background Art
[0002] As a natural polymer material, starch has broad application prospects in food packaging, pharmaceutical carriers, and agricultural films due to its renewability, biocompatibility, and degradability. However, traditional starch films have deficiencies in mechanical strength, moisture barrier properties, and weather resistance, which limits their promotion in practical applications. The mechanical properties of starch films are related to the content of amylose in the starch. Generally speaking, the more amylose there is in the starch material, the better the mechanical properties will be.
[0003] Starch film has a certain water solubility, but the solubility of the original starch film generally ranges from 10% to 30%. Research on improving the solubility of starch film has attracted the attention of researchers. Bi Huimin et al. studied an edible film that can be quickly dissolved in hot water, using potato starch as the base material, sodium carboxymethyl cellulose as the reinforcing agent, and propylene oxide as the cross-linking agent, which has good mechanical properties. Isotton et al. found that the etherified starch film with the addition of polyvinyl alcohol can be fully soluble in water and has good mechanical properties. Meng Lingru et al. added short-chain debranched waxy corn starch and mixed it with waxy corn starch to form a film, and were able to obtain a starch film with high solubility, high transparency and good strength. Although there have been many studies on improving the solubility of starch film, there are still some problems such as the mechanical properties of starch film are not high enough, or complex and expensive processes such as debranching are required, or toxic substances such as propylene oxide are added to limit its application in food. Therefore, there is no mature process for preparing edible film in industry, and starch edible film for packaging is rare on the market. The development trend of edible film preparation is moving towards a greener, simpler and more effective direction.
[0004] In summary, how to develop starch films with excellent mechanical properties and improved enzyme activity has become a technical problem that urgently needs to be solved in this field. Summary of the invention
[0005] The present invention aims to solve the above technical problems and provide a method for directionally regulating the content of straight chains in starch and improving the performance of starch film.
[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0007] A method for directionally regulating the content of straight chains in starch and improving the performance of starch films comprises the following steps:
[0008] S1. Starch modification:
[0009] The starch is dissolved in an ionic liquid at a temperature of 75-80°C, and then dried in an ozone environment to form an absolutely dry starch with a rough and bumpy surface;
[0010] S2. Preparation of pullulanase immobilized on cellulose nanofibrils:
[0011] Weigh 2-15g of absolute dry starch as a substrate, add 1.0%-10% CNF relative to the mass of starch, the dosage is 1U-10U per gram of absolute dry starch, add phosphate buffer, adjust the pH value of the mixture to 6, add 4U of Pul protein per gram of absolute dry starch, and add pullulan, and shake the mixture in a constant temperature air bath to complete the immobilization of pullulanase on cellulose nanofibrils to obtain Pul@CNF complex;
[0012] S3. Preparation of active substances:
[0013] Add polyphenols to the Pul@CNF composite and mix well, add konjac glucomannan in portions, and mix for 15-18 minutes in a pressure cooker at a pressure of 200-230 MPa and a temperature of 35-45°C;
[0014] S4, Cellulose nanofibril immobilized pullulanase system enzymatically hydrolyzes starch into film:
[0015] Take 2-8g of absolute dry starch and place it in a 250ml three-necked flask. Then add 20-80ml of distilled water and place it in a 38°C water bath. Slowly stir to disperse the starch. After fully stirring for 5 minutes, add Pul@CNF in step S3, add water to 100ml, continue stirring for 10 minutes, and heat to 95°C at a rate of 1°C / min. After reaching this temperature, add 20-80% of the mass of absolute dry starch to the solution. Plasticizer, and keep warm for 30 minutes. After stirring, remove bubbles from the obtained starch solution, spread it evenly on an acrylic plate by casting, and dry it in an oven at 50°C for 8 hours. After drying, a starch film is obtained.
[0016] Preferably, the drying time in the ozone environment is 8-10 minutes.
[0017] Preferably, the cellulose nanofibrils are one or any combination of anionic, cationic, and neutral cellulose nanofibrils.
[0018] Preferably, the pH value of the phosphate buffer is 21.
[0019] Preferably, the starch is one or any combination of corn starch, tapioca starch, potato starch and sweet potato starch.
[0020] Preferably, the cellulose nanofibrils are one or any combination of anionic, cationic, and neutral cellulose nanocrystals.
[0021] Preferably, the neutral cellulose nanocrystals have a length of 100 nm to 5000 nm, a diameter of 1 to 20 nm, and a solid content of 0.01% to 5%.
[0022] Preferably, the plasticizer is one or any combination of glycerol, urea, ethylene glycol, polyethylene glycol, propylene glycol, sorbitol, and ethanolamine.
[0023] Preferably, the mixture is placed in a constant temperature air bath shaker at 30°C and incubated at 100-300 rpm for 1-3 hours.
[0024] After adopting the above method, the present invention has the following advantages:
[0025] The present invention innovatively uses cellulose nanofibrils to immobilize pullulanase to modify starch, thereby preparing a starch film with a high amylose content. By introducing cellulose nanofibrils to immobilize pullulanase, not only the stability of pullulanase is significantly improved, but also its enzyme activity is further enhanced. This method accurately regulates the α,1-6 glycosidic bonds in amylopectin, effectively increasing the amylose content in starch. In addition, nanocellulose, as an efficient reinforcing agent, plays a key role in improving the mechanical strength and barrier properties of starch film, so that the starch-based film finally prepared has excellent mechanical properties. The present invention explores the differentiated effects of immobilized enzymes and free enzymes on the performance of starch films, and provides a theoretical basis for optimizing the performance of starch films. Through this innovative method, a solid foundation has been laid for the diversified application of starch films in the food packaging industry, and new ideas and means have also been provided for the research and development and application of environmentally friendly and degradable packaging materials.
[0026] The above summary is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present invention will be readily apparent by reference to the accompanying drawings and the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a scanning electron microscope (SEM) image of CNF-immobilized pullulanase of the present invention;
[0028] Figure 2 It is a transmission electron microscope (TEM) analysis and energy dispersive spectrum (EDS) analysis diagram of CNF-immobilized pullulanase of the present invention;
[0029] Figure 3 It is a confocal laser scanning microscope (CLSM) image of the present invention;
[0030] Figure 4 It is a schematic diagram of the principle of the present invention;
[0031] Figure 5 is the enzyme activity diagram of CNF-immobilized pullulanase of the present invention;
[0032] Figure 6 This is a basic performance diagram of a film prepared from enzyme-treated starch using CNF-fixed pullulanase of the present invention;
[0033] Figure 7 It is a deconvolution diagram within the wave number range of 800cm-1-1200cm-1 of the present invention; wherein a is an infrared spectrum diagram of starch film with different CNF addition amounts; b is an infrared spectrum diagram of starch film with different CNF addition amounts;
[0034] Figure 8 is the XRD diagram of starch film with different CNF addition amounts of the present invention;
[0035] Fig. 9 is the SEM image of starch film with different CNF addition amounts of the present invention;
[0036] Fig.10 is a graph showing the mechanical properties of starch films with different CNF addition amounts of the present invention;
[0037] Fig.11 TG graphs of starch films of the present invention; wherein a is the TG graph of starch films with different CNF addition amounts; b is the DTG graph of starch films with different CNF addition amounts;
[0038] Fig.12 is a light transmittance graph of starch films with different CNF addition amounts of the present invention;
[0039] Fig.13 is a graph of water vapor permeability coefficients of starch films of the present invention with different CNF addition amounts;
[0040] Fig.14 is a polarizing microscope image of starch film with different CNF addition amounts of the present invention;
[0041] Fig.15 is a graph of water contact angles of starch films with different CNF addition amounts of the present invention;
[0042] Fig.16 It is a phase time diagram of the suspension of the present invention; wherein a is a phase time diagram of the Pul solution and the CNF suspension; b is a phase time diagram of the CNF suspension;
[0043] Fig.17 It is the charge diagram of Pul@CNF measured by the particle charge measuring instrument of the present invention;
[0044] Fig.18 is a standard curve diagram of protein content of the present invention;
[0045] Fig.19 TEM images of the present invention; a is a TEM image of CNF; b is a TEM image of Pul@CNF; c is an enlarged TEM image of part b;
[0046] Fig. 20 TEM images of the present invention; a is a TEM image of Pul@CNF; b is a N element distribution image; c is a C, N, O element distribution image;
[0047] Fig.21 is the SEM image of Pul@CNF with different enzyme loadings of the present invention;
[0048] Fig. 22 Schematic diagram of the laser confocal microscope of the present invention; wherein a represents Pul@CNF under dark field; b represents the image of Pul@CNF under fluorescence field;
[0049] Fig.23 This is a graph showing the effect of pH on the enzymatic activities of immobilized enzymes and free enzymes of the present invention;
[0050] Fig.24 It is the effect of temperature on the enzymatic activity of immobilized enzyme and free enzyme of the present invention;
[0051] Fig.25 is a diagram of enzyme inactivation time of free enzyme and immobilized enzyme of the present invention;
[0052] Fig.26 It is the molecular weight distribution diagram of starch after enzymatic hydrolysis of the immobilized enzyme and free enzyme of the present invention;
[0053] Fig. 27 It is the XRD diagram of the film formed after the enzymatic hydrolysis of the immobilized enzyme and the free enzyme of the present invention;
[0054] Fig.28 Figure 1 is a schematic diagram of the Fourier transform attenuated total reflection infrared spectrum of the present invention; Figure a is the infrared spectrum of Pul / CNF-StF and Pul@CNF-St; Figure b is the infrared spectrum at a wave number of 800 cm -1 -1200cm -1 Deconvolution graph within range
[0055] Fig.29 : is the SEM image of Pul / CNF-StF and Pul@CNF-StF of the present invention;
[0056] Fig.30 It is the mechanical properties diagram of Pul / CNF-StF and Pul@CNF-StF of the present invention;
[0057] Fig.31 : is the thermogravimetric analysis result diagram of the present invention; wherein a is the TG curve of Pul / CNF-StF and Pul@CNF-StF; b is the DTG curve of Pul / CNF-StF and Pul@CNF-StF; DETAILED DESCRIPTION
[0058] The present invention is further described in detail below in conjunction with the full text.
[0059] Combined with Figure 1-Figure 6 , a method for directionally regulating the content of straight chain in starch and improving the performance of starch film, comprising the following steps:
[0060] S1. Starch modification:
[0061] The starch is dissolved in an ionic liquid at a temperature of 75-80°C, and then dried in an ozone environment to form an absolutely dry starch with a rough and bumpy surface;
[0062] S2. Preparation of pullulanase immobilized on cellulose nanofibrils:
[0063] Weigh 2-15g of absolute dry starch as a substrate, add 1.0%-10% CNF relative to the mass of starch, the dosage is 1U-10U per gram of absolute dry starch, add phosphate buffer, adjust the pH value of the mixture to 6, add 4U of Pul protein per gram of absolute dry starch, and add pullulan, and shake the mixture in a constant temperature air bath to complete the immobilization of pullulanase on cellulose nanofibrils to obtain Pul@CNF complex;
[0064] Optimization of reaction conditions: The above mixture was placed in a constant temperature air bath set at 30°C and shaken at a constant speed of 160 rpm for 6 hours to promote the adsorption and binding of Pul protein on the CNF surface to form Pul@CNF nanocomposite materials.
[0065] Efficient purification step: After the reaction, Pul@CNF is continuously washed with a phosphate buffer solution at a concentration of 0.04 mol / L and a pH of 6. This step ensures the purity of the Pul@CNF nanocomposite by replacing the fresh washing solution several times and separating the solid and liquid phases by centrifugation or filtration until no free Pul protein molecules can be detected in the washing solution.
[0066] S3. Preparation of active substances:
[0067] Add polyphenols to the Pul@CNF composite and mix well, add konjac glucomannan in portions, and mix in a pressure cooker at a pressure of 200-230 MPa and a temperature of 35-45°C for 15-18 min;
[0068] S4, Cellulose nanofibril immobilized pullulanase system enzymatically hydrolyzes starch into film:
[0069] Take 2-8g of absolute dry starch and place it in a 250ml three-necked flask. Then add 20-80ml of distilled water and place it in a 38°C water bath. Slowly stir to disperse the starch. After fully stirring for 5 minutes, add Pul@CNF in step S3, add water to 100ml, continue stirring for 10 minutes, and heat to 95°C at a rate of 1°C / min. After reaching this temperature, add 20-80% of the mass of absolute dry starch to the solution. Plasticizer, and keep warm for 30 minutes. After stirring, remove bubbles from the obtained starch solution, spread it evenly on an acrylic plate by casting, and dry it in an oven at 50°C for 8 hours. After drying, a starch film is obtained.
[0070] The drying time in the ozone environment is 8-10 minutes.
[0071] The cellulose nanofibrils are one or any combination of anionic, cationic, and neutral cellulose nanofibrils.
[0072] The pH value of the phosphate buffer is 21.
[0073] The starch is one or any combination of corn starch, tapioca starch, potato starch and sweet potato starch.
[0074] The cellulose nanofibrils are one of anionic, cationic, and neutral cellulose nanocrystals or any combination thereof, and the cellulose nanofibrils are CNFs.
[0075] The neutral cellulose nanocrystal has a length of 100nm-5000nm, a diameter of 1-20nm and a solid content of 0.01%-5%.
[0076] The plasticizer is one or any combination of glycerol, urea, ethylene glycol, polyethylene glycol, propylene glycol, sorbitol, and ethanolamine.
[0077] The mixture was placed in a constant temperature air bath shaker at 30°C and incubated at 100-300 rpm for 1-3 h.
[0078] When the present invention is implemented, adding polyphenols can improve the retrogradation and digestion and absorption performance of starch, and form a complex with starch, thereby affecting its physical and chemical properties. Polyphenols have more hydroxyl groups and can interact with the polar groups of polypeptides through hydrogen bonds, while polyphenols containing hydrophobic substituents bind to proteins through hydrophobic interactions. In addition, methylated polyphenols with lower polarity can penetrate into the hydrophobic region of proteins and interact with them. The driving force dominated by non-covalent interactions is hydrophobic interactions. In the process of protein and polyphenol compounding, there are also weaker non-covalent interactions such as electrostatic force and van der Waals force, which generally play a stabilizing and auxiliary role.
[0079] Proteins and polyphenols are more likely to interact covalently. Phenolic compounds are more active and are easily oxidized to form quinones. Quinones can react with some free amino groups of proteins to form covalent bonds through Michael addition reactions, or carbon cations formed by phenol cleavage can undergo cross-linking reactions with exogenous polypeptide chains. In addition, there is also a process in which free radicals mediate the formation of polyphenol-protein covalent complexes. The number of hydroxyl groups and aromatic rings of polyphenols determines the degree of covalent interaction with proteins. It is worth noting that the same substance may bind in different ways in different environments.
[0080] Both starch and polyphenols contain a large number of hydroxyl groups. The interactions between starch and polyphenols include non-covalent interactions such as hydrogen bonds, electrostatic interactions, hydrophobic interactions, and ionic bonds, and the strength of the interactions is affected by their structural characteristics and physicochemical parameters. At the molecular level, the interactions between various polyphenols and starch can produce two types of complexes: one type is a V-type complex; the other is a non-inclusion complex. In addition, polyphenols can interact with enzymes related to starch digestion, producing competitive or non-competitive inhibition, thereby regulating the hydrolysis of starch.
[0081] The impact on the functional properties of starch is mainly reflected in the change of its digestibility. Digestion is an important part of starch's function. It is generally believed that long-term intake of large amounts of rapidly digestible starch will pose risks to human health and increase the possibility of metabolic diseases. The inhibitory effect of polyphenols on starch digestion is due to the formation of new crystalline structures and non-competitive inhibition. Polyphenols interact with starch to form V-type complexes, and can also react with enzymes that digest starch, which is also attributed to the interaction between proteins and polyphenols. In addition, the tendency of amylose to regenerate will lead to unstable starch-polyphenol V-type complexes, which may release polyphenol compounds to inhibit the activity of α-amylase or competitively inhibit the activity of glucose transporters.
[0082] In terms of starch gelatinization, protein has the function of delaying starch gelatinization and regulating the retrogradation process of amylose and amylopectin. Protein can attach to the starch and hinder the interaction between starch and solvent through physical action, thus regulating the expansion and dissolution of starch granules.
[0083] After being dissolved in ionic liquid, the surface morphology of starch particles changes from the smooth surface of the original starch to rough and bumpy, so as to increase the reaction contact area and improve the reaction efficiency.
[0084] Ozone is a strong oxidant. Its extra oxygen atom makes it leave no residue during the oxidation process compared with conventional oxidants such as hypochlorite, potassium permanganate, and periodic acid, which meets the requirements of green chemistry. During the ozone oxidation process, the carboxyl and carbonyl contents increase with the extension of ozone exposure time, and the degree of starch oxidation of starch from different sources is different. Starch was exposed to ozone for 10 minutes at different ozone generation times. The average molecular weight of starch decreased, while the average molecular weight of oxidized cassava starch increased. All oxidized starches exhibited non-Newtonian shear thinning behavior. With the increase of ozone generation time, the viscosity of starch decreased sharply. Compared with unmodified starch, there was no difference in the gelatinization temperature and gelatinization enthalpy of all oxidized starches. After 1 minute of ozone treatment, the regeneration enthalpy of starch increased significantly.
[0085] Konjac glucomannan has a significant effect on the rheological properties, retrogradation properties and digestion properties of starch. Adding KGM to starch foods can give the food better performance, such as improving its rheological properties and digestion properties. It produces active substances to affect the physical and chemical properties of starch, thereby improving its functional properties.
[0086] The structure and properties of starch are affected by multiple mechanisms, including physical, chemical and biochemical pathways. These changes not only improve the functional properties of starch, but also provide new possibilities for its application in the food industry.
[0087] Embodiment 1:
[0088] The method for directionally regulating the content of straight chain in starch and improving the performance of starch film comprises the following steps:
[0089] S1. Starch modification:
[0090] The starch is dissolved in an ionic liquid at a temperature of 80°C, and then dried in an ozone environment to form an absolutely dry starch with a rough and bumpy surface;
[0091] S2. Preparation of pullulanase immobilized on cellulose nanofibrils:
[0092] Weigh 5 g of absolute dry starch as a substrate, add 8% CNF relative to the mass of starch, and the dosage is 8U per gram of absolute dry starch, add phosphate buffer, adjust the pH value of the mixture to 6, add 4U of Pul protein per gram of absolute dry starch, and add pullulan, and shake the mixture in a constant temperature air bath to complete the immobilization of pullulanase on cellulose nanofibrils to obtain Pul@CNF composite;
[0093] S3. Preparation of active substances:
[0094] Polyphenols were added to the Pul@CNF composite and mixed evenly, and konjac glucomannan was added in portions and mixed for 15 min in a pressure cooker at a pressure of 200 MPa and a temperature of 35 °C;
[0095] S4, Cellulose nanofibril immobilized pullulanase system enzymatically hydrolyzes starch into film:
[0096] Take 5g of absolute dry starch and put it in a 250ml three-necked flask, then add 80ml of distilled water and put it in a 38℃ water bath environment, slowly stir to disperse the starch, stir well for 5min, add Pul@CNF in step S3, add water to 100ml, continue stirring for 10min, and heat to 95℃ at a rate of 1℃ / min. After reaching this temperature, add 50% of the absolute dry starch mass of plasticizer to the solution, and keep warm for 30min. After stirring, remove bubbles from the obtained starch solution, spread it evenly on an acrylic plate by casting, and dry it in an oven at 50℃ for 8h. After drying, a starch film is obtained.
[0097] Embodiment 2:
[0098] The method for directionally regulating the content of straight chain in starch and improving the performance of starch film comprises the following steps:
[0099] S1. Starch modification:
[0100] The starch is dissolved in an ionic liquid at a temperature of 80°C, and then dried in an ozone environment to form an absolutely dry starch with a rough and bumpy surface;
[0101] S2. Preparation of pullulanase immobilized on cellulose nanofibrils:
[0102] Weigh 5 g of absolute dry starch as a substrate, add 8% CNF relative to the mass of starch, and the dosage is 8U per gram of absolute dry starch, add phosphate buffer, adjust the pH value of the mixture to 6, add 4U of Pul protein per gram of absolute dry starch, and add pullulan, and shake the mixture in a constant temperature air bath to complete the immobilization of pullulanase on cellulose nanofibrils to obtain Pul@CNF composite;
[0103] S3. Preparation of active substances:
[0104] Polyphenols were added to the Pul@CNF composite and mixed evenly, and konjac glucomannan was added in portions and mixed for 18 min in a pressure cooker at a pressure of 210 MPa and a temperature of 36 °C;
[0105] S4, Cellulose nanofibril immobilized pullulanase system enzymatically hydrolyzes starch into film:
[0106] Take 5g of absolute dry starch and put it in a 250ml three-necked flask, then add 80ml of distilled water and put it in a 38℃ water bath environment, slowly stir to disperse the starch, stir well for 5min, add Pul@CNF in step S3, add water to 100ml, continue stirring for 10min, and heat to 95℃ at a rate of 1℃ / min. After reaching this temperature, add 50% of the absolute dry starch mass of plasticizer to the solution, and keep warm for 30min. After stirring, remove bubbles from the obtained starch solution, spread it evenly on an acrylic plate by casting, and dry it in an oven at 50℃ for 8h. After drying, a starch film is obtained.
[0107] The starch film prepared by the above steps is named Pul@CNF-StF. The method of the present invention not only improves the stability and activity of pullulanase, but also improves the mechanical properties and barrier properties of the starch film through the reinforcement effect of nanocellulose, providing an environmentally friendly and degradable material option for the food packaging field.
[0108] The present invention discloses a method for preparing pullulanase (Pul) immobilized by cellulose nanofibrils (CNF), and the application of the immobilized enzyme in the process of starch enzymatic hydrolysis and film formation. The technology improves the efficiency of starch enzymatic hydrolysis through innovative enzyme immobilization methods, thereby optimizing the preparation process of biodegradable materials, especially starch-based films. This field integrates nanomaterial science, enzyme engineering technology, and polymer material processing technology, aiming to provide an efficient and sustainable solution for the manufacture of environmentally friendly materials.
[0109] Embodiment three:
[0110] Detection of immobilized enzymes:
[0111] 1.5% CNF (relative to 5g absolute dry starch) and 4U / g (relative to 5g absolute dry starch) Pul were adjusted to pH=6 with phosphate buffer, and the mixture was shaken at a constant speed of 160rmp for 6h in a constant temperature air bath at 30°C to obtain Pul@CNF. The Pul@CNF was continuously washed with phosphate buffer at a concentration of 0.04mol / L and a pH of 6 to ensure that no protein molecules could be detected in the washing solution, thereby obtaining pure Pul@CNF.
[0112] Under the conditions of pH 2-8 and temperature 60° C., the enzyme was reacted with 2% (w / v) pullulan substrate for 30 minutes, and the enzyme activity was measured to obtain the optimal reaction pH value of the enzyme.
[0113] The enzyme was reacted with 2% (w / v) pullulan substrate at 30-80°C for 30 min, the enzyme activity was measured, and the optimal reaction temperature of the enzyme was obtained.
[0114] 20U of Pul was added to 0.075g of absolutely dry CNF for immobilization, and 20U of free Pul was used as the control group for a 7-day stability test. The enzyme activity was tested regularly every day, and the relative enzyme activity was calculated based on the Pul enzyme activity on the first day for comparison.
[0115] Embodiment 4:
[0116] Effects of free and immobilized pullulanase on the film-forming properties of hydrolyzed starch.
[0117] Cellulose nanofibril immobilized pullulanase system enzymatically hydrolyzes starch into film: Take 5g of absolute dry starch and place it in a 250ml three-necked flask and round-bottom flask, then add 50ml of distilled water and place it in a 38℃ water bath, slowly stir to disperse the starch, stir thoroughly for 5min, add Pul@CNF prepared in 4.3.1, add water to 100ml, continue stirring for 10min, and heat to 95℃ at a rate of 1℃ / min. After reaching this temperature, add 40% glycerol (accounting for the absolute dry starch mass) and keep warm for 30min. After stirring. Remove bubbles from the obtained starch solution, spread it evenly on the acrylic plate by casting, and put it in a 50℃ oven for drying for 8h. After drying, remove the film from the acrylic plate and store it for 48h at a temperature and relative humidity (RH) of 25℃ and 50% respectively for further use. The starch film prepared by immobilized enzyme is named Pul@CNF-StF.
[0118] Take 1 portion of 5g of absolute dry starch and place it in a 250ml three-necked flask. Then add 50ml of distilled water and place it in a 38°C water bath. Stir slowly to disperse the starch. After fully stirring for 5 minutes, add 1.5%, add water to 100ml, continue stirring for 5 minutes, and heat to 95°C at a rate of 1°C / min. After reaching this temperature, add 40% glycerol (relative to the mass of absolute dry starch) and keep warm for 30 minutes. After stirring, remove bubbles from the resulting starch solution, spread it evenly on the acrylic plate by casting, and put it in a 50°C oven for drying for 8 hours. After drying, remove the film from the acrylic plate and store it for 48 hours at a temperature and relative humidity (RH) of 25°C and 50% respectively for further use.
[0119] Test experiment:
[0120] Cellulose nanofibrils were added to the starch solution treated with Pul to prepare a starch composite film with excellent performance. By systematically exploring the effect of CNF addition on the performance of starch composite films, starch composite film materials with excellent mechanical properties, barrier properties and biodegradability were prepared.
[0121] Experimental materials and reagents:
[0122] The raw materials used in this experiment are: ordinary corn starch provided by Zhejiang Jingxing Company, with a water content of 12.2%. Cellulose nanofibrils (CNF: length 100-5000nm; width 1-20nm; concentration 0.5-5%; cationic charge density, 0.2-1.5mmol / g) provided by Zhejiang Jinjiahao Green Nanomaterials Co., Ltd. The main reagents used in this experiment are shown in Table 1-1:
[0123] Table 1-1 Experimental reagents
[0124]
[0125] Experimental instruments and equipment:
[0126] The instruments and specifications used in this experiment are shown in Table 1-2:
[0127] 1-2 Main instruments and equipment used in the experiment
[0128]
[0129]
[0130] Preparation of cellulose nanofibril starch film (CNF / Pul-StF):
[0131] Take 6 portions of 5g of absolute dry starch and place them in a 250ml three-necked flask, then add 50ml of distilled water and place them in a 38℃ water bath. Stir slowly to disperse the starch. After fully stirring for 5min, add 4U / g of Pul (relative to the mass of absolute dry starch) to the above 6 portions of starch suspension, and continue stirring for 5min. Then add 0%, 0.5%, 1.0%, 1.5%, 2%, and 2.5% of cellulose nanofibrils (CNF) (relative to the mass of absolute dry starch) to 6 three-necked round-bottom flasks, add water to 100ml, continue stirring for 5min, and heat to 95℃ at a rate of 1℃ / min. After reaching this temperature, add 40% glycerol (relative to the mass of absolute dry starch) and keep warm for 30min. After stirring, remove bubbles from the resulting starch solution, spread it evenly on an acrylic plate by casting, and dry it in an oven at 50℃ for 8h. After drying, the film was removed from the acrylic plate and stored at 25°C and 50% relative humidity (RH) for 48 h for further use. The six starch films were named as follows: (1) Pul-StF, (2) 0.5% CNF / Pul-StF, (3) 1.0% CNF / Pul-StF, (4) 1.5% CNF / Pul-StF, (5) 2.0% CNF / Pul-StF, and (6) 2.5% CNF / Pul-StF.
[0132] Fourier transform attenuated total reflectance infrared spectroscopy (ATR-FTIR) analysis:
[0133] like Figure 7 As shown in the figure, the infrared spectrum does not change significantly after adding CNF. There is no chemical bonding between the molecules in the starch and CNF. In addition, the quaternary ammonium groups on CNF are not detected, which means that the quaternary ammonium groups on CNF have a low content and a weak signal in the infrared spectrum, which is masked by the strong signal of starch and is therefore difficult to detect.
[0134] From the analysis of Table 1-3, it can be seen that when the CNF addition amount is 0.5%-1.5%, the ratio of the ordered structure also shows an increasing trend with the increase of CNF addition, although the increase is relatively small. It shows that CNF nanocellulose has good compatibility and dispersibility in starch film, and can interact with starch molecular chains more effectively to form a short-range ordered structure. When the CNF addition amount in the starch film is 1.5%, the ratio of the spiral ordered structure reaches the highest point of 0.560, indicating that the structure is arranged in an orderly manner at this time, the intermolecular bonding is the closest, and it has a greater impact on the starch film mechanics. When the CNF addition amount is ≥2.0%, it may have an adverse effect on the starch structure, especially when the addition amount reaches 2.5%, the damage to the ordered structure is particularly significant. This has an impact on the structure of the starch film. It shows that the appropriate addition of CNF to the starch film can enhance the short-range ordered structure in the starch film after Pul enzymatic hydrolysis, and also have a corresponding effect on the subsequent mechanical properties.
[0135] Table 1-3 Ratio of absorbance at 1046cm-1 / 1022cm-1 after deconvolution of infrared spectrum of starch film
[0136]
[0137] Wide-angle X-ray diffraction (XRD) pattern analysis:
[0138] like Figure 8 As shown in the figure, after adding CNF, a new peak is generated at 2θ=15°, and the peak intensity increases with the increase of CNF. The content of amylose in the starch film after Pul enzymatic hydrolysis will increase, and amylose molecules tend to form more helical structures and helical ordered structures. The addition of CNF may interact with amylose molecules, further promote the formation of helical structures, and form new ordered crystals. When the amount of CNF added is greater than 1.5%, the peak intensity is weakened, which may be due to the agglomeration of CNF affecting the helix of CNF and amylose, causing the peak intensity to weaken.
[0139] The XRD spectrum data was processed by Jeda6.5 software and the crystallinity of the starch film was calculated to obtain Table 1-4. From the analysis of Table 1-4, it can be seen that the crystallinity of the Pul-StF sample after Pul treatment was greatly reduced to 13.51%, while the crystallinity gradually increased after adding CNF, indicating that the appropriate addition of CNF can increase the crystallinity of the starch film. CNF itself has a high crystallinity and can improve the crystallinity performance of starch film materials. At the same time, CNF interacts with the starch chains in the starch film, improves the short-range order of the starch film, and improves the crystallinity. When the CNF addition amount is greater than 1.5%, the agglomeration of CNF makes the starch distribution uneven, thereby affecting the formation of crystals in the starch and reducing the crystallinity of the starch material. It shows that the appropriate addition of CNF can effectively improve the crystallinity of the starch film.
[0140] Table 1-4 Crystallinity of starch films with different CNF addition amounts
[0141]
[0142]
[0143] Scanning electron microscope (SEM) observation:
[0144] like Fig. 9 As shown in the plane, the surface of the film formed by the starch modified by Pul (Pul(-StF)) is uniform and dense. When the CNF addition amount is less than 2.0%, the surface of the starch film obtained has a uniform and flat structure. When the CNF addition amount is 1.5%, the surface of the starch film is flat and smooth. When the CNF addition amount is ≥2.0%, the starch film becomes rough and unevenly distributed. When the CNF addition amount exceeds a certain limit, the surface and cross-sectional structure of the starch film will change significantly, indicating that too much CNF will agglomerate and make the surface of the starch film rough and the cross-section become uneven. Due to the imaging characteristics of the SEM image and possible differences in the sample preparation process, these agglomeration phenomena may not be directly apparent in the SEM image of the starch film.
[0145] like Fig. 9 As shown in the cross section, a slight layered structure appears after adding CNF to the starch film. This is because CNF promotes the debranching and hydrolysis behavior of Pul on starch molecules. During this process, CNF can form a tight structure with long / short starch molecular chains, improve the mechanical properties of the starch film, and form a certain layered structure in the macroscopic cross section. However, when the amount of CNF added increases, the CNF-StF starch film becomes rougher. When the addition amount is ≥2.0% CNF, the surface has a fibrous protrusion structure, and the aggregate structure of cellulose nanofibril particles can also be seen in its cross section. This is because CNF molecules contain more hydroxyl groups, and hydrogen bonds are easily formed between molecules, which causes cellulose to agglomerate. . It shows that the appropriate addition of CNF to starch can effectively improve the structure and properties of starch film. Too much will lead to roughness of the film surface and agglomeration of cellulose.
[0146] Mechanical properties analysis:
[0147] From the analysis of Tables 1-5, it can be seen that the elongation at break of the starch film (Pul-StF) after enzymatic hydrolysis is higher, while the mechanical properties of the starch film with added CNF are better. With the increase of the amount of CNF added, the tensile strength first increases and then decreases. This phenomenon is due to the high specific surface area and strong hydrogen bonding ability of CNF. When CNF is added to the starch film, CNF can form strong hydrogen bonds with the straight-chain starch molecules, reduce the fluidity between the starch film, and effectively increase the mechanical strength of the film. When the amount of CNF added to the starch film is 1.5%, the mechanical properties reach 8.74MPa.
[0148] Table 1-5 Mechanical properties of starch films with different CNF addition amounts
[0149] Thickness(mm) Tensile strength(MPa) Elongation at break (%) Pul-StF 0.110 5.60 52.30 0.5% CNF / Pul-StF 0.120 6.75 56.74 1.0%CNF / Pul-StF 0.110 7.44 44.06 1.5% CNF / Pul-StF 0.125 8.74 38.72 2.0%CNF / Pul-StF 0.117 7.57 34.40 2.5% CNF / Pul-StF 0.115 7.15 25.57
[0150] like Fig.10 As shown in the figure, when ≥2.0% CNF is added, the tensile strength of the starch film material decreases, which may cause CNF to form agglomerates or aggregates in the starch liquid, affecting the orderly arrangement of starch molecules and weakening the tight binding of starch and starch and CNF hydrogen bonds. CNF can enhance the mechanical properties of starch film, but excessive CNF may destroy the original structure between starch molecules, causing the mechanical properties of starch to decrease.
[0151] Thermogravimetric (TG) analysis:
[0152] like Fig.11 As shown, starch film TG Figure 3 It is mainly divided into three decomposition stages. The third stage is 290℃-600℃, which is the degradation change of starch. In this temperature range, the weight loss of Pul / CNF-StF is smaller than that of Pul-StF, indicating that the amylose produced by Pul interacts with CNF to generate substances with stronger thermal stability, which increases the residue. This may also be because CNF has good thermal stability, which increases the residue. However, it can be seen from the figure that the change trend of the residue is complicated with the increase of CNF content, indicating that it is not simply the addition of CNF that increases the residue. However, from the overall level, adding CNF to the starch film can increase the residue and enhance the thermal stability.
[0153] In order to fully understand the thermal behavior of the different composite films studied, the first derivative TGA curves were calculated, such as Fig.11As shown. After adding CNF, the maximum decomposition temperature shifted slightly to the right (310℃-314℃), indicating that CNF can slightly increase the stability of starch film. This is because CNF forms a composite structure with amylose in the starch film, which makes the interaction between starch chains closer, and then the decomposition temperature rises. By adding cellulose nanofibrils (CNF) to thermoplastic starch (TPS), the thermal stability of starch film is improved. This shows that CNF can effectively improve the thermal stability of starch film.
[0154] Transmittance analysis:
[0155] like Fig.12 As shown in the figure, when 0.5%-2.5% CNF is added to the starch film, the light transmittance continues to decrease. The slender CNF fibers are easy to form a network structure in the starch film, changing the internal structure of the starch film, thereby affecting the ability of light or gas molecules to pass through the film. At the same time, CNF itself has light absorption properties, which may also cause vibration, resonance and other phenomena inside the starch film, further promoting the scattering and absorption of light.
[0156] Water vapor transmission coefficient analysis:
[0157] like Fig.13 As shown in the figure, with the addition of CNF (0.5%-1.5%), the water vapor permeability coefficient decreases. When CNF (2.0%-2.5%) is continued to be added, the water vapor permeability increases. CNF can form a dense network structure with starch molecules. Water molecules have to go through a more tortuous path through the starch film, resulting in a decrease in the water vapor permeability coefficient. When the cellulose nanofibrils exceed 1.5%, the water vapor permeability coefficient increases. Excessive CNF agglomeration will affect the changes in the pore structure inside the starch film, destroying the continuity of the starch film, allowing water vapor to pass through these gaps, resulting in an increase in the water vapor permeability coefficient. This shows that CNF can effectively improve the water vapor permeability coefficient of the starch film.
[0158] Polarizing microscope observation:
[0159] like Fig.14 As shown in the figure, as the amount of CNF increases, CNF in the starch film begins to aggregate and agglomerate over a large area. When the addition amount of CNF reaches 1.5%, aggregation can be observed. This aggregation phenomenon becomes more obvious when the addition amount reaches 2.5%. The aggregates destroy the uniformity and continuity of the starch film. This proves again Fig. 9 When CNF addition exceeded 1.5%, starch caused a decrease in mechanical properties; Fig.13 The reason for the increase in water vapor transmission is that when preparing starch films, the amount of CNF added needs to be reasonably controlled to avoid the adverse effects of aggregation and thus optimize the performance of the film.
[0160] Contact Angle Analysis:
[0161] like Fig.15 As shown in the figure, with the continuous increase of CNF concentration, the water contact angle of starch film first increases and then remains stable, with the maximum water contact angle being 66.3°. Figure 2-10 Compared with starch films without CNF addition, the nanocellulose starch film increased by about 200% because CNF changed the microstructural morphology of the starch film, reducing its surface tension and increasing the contact angle.
[0162] The present invention studies the effect of the dosage of cellulose nanofibrils (CNF) on the performance of starch film after Pul, laying the foundation for the application of cellulose nanofibrils (CNF) immobilized pullulanase (Pul). Adding CNF to enzymatic starch to prepare starch film effectively improves the performance of starch film. When the dosage of CNF reaches 1.5%, the mechanical properties, contact angle and thermal stability of the starch film are improved, from 5.61MPa, 17.7°, 310°C to 8.74MPa, 66.3°, 314°C respectively. And the barrier performance is improved, and the water vapor permeability coefficient is reduced from 7.3710-12g·cm / Pa·s·cm2 to 6.33×10-12g·cm / Pa·s·cm2.
[0163] The addition of CNF improved the mechanical properties, thermal stability, light transmittance and water vapor permeability of the starch film. In particular, when the CNF dosage was 1.5%, the mechanical properties of the starch film were particularly outstanding. This study provides the optimal CNF dosage for the application of CNF immobilized Pul.
[0164] Determining the optimal conditions for the dosage of pullulanase and nanocellulose in starch film provides an important basis for subsequent composite system research. Through these basic conditions, we understand the mechanism of the influence of pullulanase and nanocellulose on the performance of starch film, and provide guidance for optimizing the ratio of these two components in the composite system. Although these conditions may not be optimal in the composite system, they provide a starting point for further exploration and optimization in nanocellulose immobilized enzymes.
[0165] In this study, cellulose nanofibrils (CNF) were used to immobilize pullulanase (Pul), thereby forming a Pul@CNF complex. In order to gain a deeper understanding of the effect of the immobilization process on the enzymatic properties, the properties of Pul@CNF and free enzymes were compared in detail. The optimal reaction temperature, optimal pH value, and stability of these two forms of enzymes under optimal temperature and pH conditions were systematically studied. In addition, starch was treated with immobilized Pul@CNF and filmed. The performance of the starch film formed by starch treated with free enzyme was compared to evaluate the effect and potential advantages of immobilized pullulanase in practical applications.
[0166] Experimental materials and reagents:
[0167] The raw materials used in this experiment are mainly corn starch provided by Zhejiang Jingxing Paper Industry, with a moisture content of 12.2%. Cellulose nanofibrils (CNF: length 100-5000nm; width 1-20nm; concentration 0.5-5%; cationic charge, 0.2-1.5mmol / g) provided by Zhejiang Jinjiahao Green Nanomaterials Co., Ltd.
[0168] Table 2-1 Experimental reagents
[0169]
[0170]
[0171] Experimental instruments and equipment:
[0172] Table 2-2 Main instruments and equipment used in the experiment
[0173]
[0174]
[0175] Experimental methods.
[0176] Preparation of cellulose nanofibrils immobilized with pullulanase (Pul@CNF):
[0177] The standard curve was prepared by Bradford method. Standard protein solutions of different concentrations were prepared, Coomassie Brilliant Blue reagent was added, the absorbance at a wavelength of 595 nm was measured, and the protein standard curve was drawn.
[0178] 1.5% CNF (relative to 5g absolute dry starch) and 4U / g (relative to 5g absolute dry starch) Pul were adjusted to pH=6 with phosphate buffer, and the mixture was shaken at a constant speed of 160rmp for 6h in a constant temperature air bath at 30°C to obtain Pul@CNF. The Pul@CNF was continuously washed with phosphate buffer at a concentration of 0.04mol / L and a pH of 6 to ensure that no protein molecules could be detected in the washing solution, thereby obtaining pure Pul@CNF.
[0179] Zeta potential determination:
[0180] Pul and CNF were diluted into certain solutions respectively, and the tested solutions were injected into electrodes with voltage applied at both ends, and then measured with a Zeta potential meter.
[0181] Particle Charge Determination (PCD) Measurement:
[0182] Take 8 portions of 0.075g (solid content) CNF suspension and place them in a 20ml sample bottle, gradually add different amounts of pullulanase (0U, 10U, 30U, 40U, 50U, 70U, 120U, 140U), and observe the changes in the sample. Weigh a certain mass of the obtained sample and place it in the test cup of the particle charge meter, add 10mL of deionized water, install the test cup to the corresponding position of the instrument, start the instrument, and select the corresponding standard titrant for titration according to the displayed potential value. The calculation formula for the sample charge density in this experiment is as follows:
[0183]
[0184] Where: q is the specific charge, mmol / L; V1 is the volume of PDADMAC (or PesNa) standard titrant consumed, mL; m is the mass of the sample, g; CPDADMAC (or PesNa) standard titrant concentration, mmol / L. Note: If the sample is negatively charged, use PDADMAC standard solution (10-3mol / L) for titration; if the sample is positively charged, use PesNa standard solution (10-3mol / L) for titration.
[0185] Analysis of Pul@CNF carrier fixed amount:
[0186] Measuring the loading of immobilized enzyme: Determined by calculating the total amount of protein added at the beginning of the reaction and subtracting the amount of unimmobilized protein in the supernatant and washes
[0187] Where Em0 is the total amount of protein added initially, and Em1 is the mass of protein detected in the solution after fixation.
[0188] TEM was used to characterize the surface morphology of CNF and Pul@CNF. The CNF and Pul@CNF suspensions were diluted 1000 times and then immediately dropped onto the ultra-thin carbon film to prepare the samples, which were then observed after being left overnight.
[0189] Scanning Electron Microscope (SEM) Analysis:
[0190] The microstructure of Pul@CNF was characterized by SEM. Freeze-dried CNF and Pul@CNF were dispersed and suspended on a clean silicon wafer, air-dried and then sprayed with gold.
[0191] Confocal laser scanning microscopy (CLSM) analysis:
[0192] The Pul@CNF was characterized by laser scanning confocal microscopy (CLSM) (FV1000, OlympUs, Tokyo, Japan). Pullulanase and fluorescein isothiocyanate (FITC) were weighed at an absolute dry mass ratio of 100:0.08, and the whole process was performed under dim light. The conical flask containing the mixed solution was wrapped with tin foil and placed in a constant temperature air bath shaker at 25°C for 6 hours to obtain FITC-labeled pullulanase. The labeled pullulanase was fixed to CNF according to the method of 4.3.1.
[0193] Pul@CNF enzymatic performance analysis:
[0194] Enzyme activity assay:
[0195] Weigh 1g of enzyme sample, accurate to ±0.0001g or take 1mL of enzyme sample, accurate to 0.01mL, dissolve it in acetic acid-sodium acetate buffer, mix it with magnetic stirring, accurately dilute it to volume and let it stand for 10min before testing. Take four 25mL graduated stoppered test tubes (one blank tube and three sample tubes), accurately add preheated 1.00mL of pullulan solution to each of the four tubes, and place the test tubes in a 60℃±0.1℃ water bath to preheat for 10min; add 1.0mL of diluted enzyme solution to be tested to each of the three sample tubes at a certain time interval (no addition to the blank tube), accurately time the reaction, and take them out one by one after 30min; immediately add 3.0mL of DNS reagent to each test tube and shake to mix; add 1.0mL of enzyme solution to be tested to the blank tube; put the four tubes into a boiling water bath at the same time, take them out after heating for 7min, quickly cool to room temperature, add 10mL of water, and shake well; adjust the instrument zero point with the solution in the blank tube (control solution), measure the absorbance of the solution at a wavelength of 550nm with a spectrophotometer, and take the average value; use the average absorbance value to check the glucose content of the standard curve.
[0196] Determination of the optimal pH value of enzyme reaction:
[0197] Under the conditions of pH 2-8 and temperature 60° C., the enzyme was reacted with 2% (w / v) pullulan substrate for 30 minutes, and the enzyme activity was measured to obtain the optimal reaction pH value of the enzyme.
[0198] Determination of the optimal reaction temperature of enzyme:
[0199] The enzyme was reacted with 2% (w / v) pullulan substrate at 30-80°C for 30 min, the enzyme activity was measured, and the optimal reaction temperature of the enzyme was obtained.
[0200] Pul@CNF stability analysis:
[0201] 20U of Pul was added to 0.075g of absolutely dry CNF for immobilization, and 20U of free Pul was used as the control group for a 7-day stability test. The enzyme activity was tested regularly every day, and the relative enzyme activity was calculated based on the Pul enzyme activity on the first day for comparison.
[0202] Effect of Pul@CNF on starch film:
[0203] Effects of free pullulanase and immobilized pullulanase on film-forming properties of hydrolyzed starch:
[0204] Cellulose nanofibril immobilized pullulanase system enzymatically hydrolyzes starch into film: Take 5g of absolute dry starch and place it in a 250ml three-necked flask and round-bottom flask, then add 50ml of distilled water and place it in a 38℃ water bath, slowly stir to disperse the starch, stir thoroughly for 5min, add Pul@CNF prepared in 4.3.1, add water to 100ml, continue stirring for 10min, and heat to 95℃ at a rate of 1℃ / min. After reaching this temperature, add 40% glycerol (accounting for the absolute dry starch mass) and keep warm for 30min. After stirring. Remove bubbles from the obtained starch solution, spread it evenly on the acrylic plate by casting, and put it in a 50℃ oven for drying for 8h. After drying, remove the film from the acrylic plate and store it for 48h at a temperature and relative humidity (RH) of 25℃ and 50% respectively for further use. The starch film prepared by immobilized enzyme is named Pul@CNF-StF.
[0205] The starch film prepared by free enzyme hydrolysis was prepared according to the method of 3.3.1, and the amount of CNF was 1.5%. The starch film prepared by free enzyme was named Pul / CNF-StF.
[0206] Gel Permeation Chromatography with Multi-Angle Light Scattering (GPC-MALS):
[0207] The molecular weight distribution of starch after enzymatic hydrolysis by immobilized enzyme and free enzyme was determined by gel chromatography. First, 9 mg of starch sample was accurately weighed, 3 mL of dimethyl sulfoxide (DMSO) was added, and dissolved overnight at 100 ° C. All solutions used in this experiment were filtered through a 0.45 μm PTFE filter membrane. The flow rate was 0.3 mL / min and the injection volume was 500 μL. All data were recorded and evaluated using PSS WinGPC UniChrom software (PSSPolymer Standards Service, Mainz, Germany).
[0208] Zeta potential determination of raw material charge:
[0209] like Fig.16As shown in a, the Zeta potential of the pullulanase solution fluctuates between positive potentials and presents a negative potential. The negative potential or charge comes from the carboxyl group, while the negative potential of the cellulose nanofibril suspension fluctuates and presents a positive potential. The positive potential comes from the quaternary ammonium salt groups modified on the surface of the cellulose nanofibrils. The Zeta of the Pul solution and the CNF suspension shows that the surface of the enzyme molecule and the surface of the CNF cellulose molecule present opposite charges. Due to electrostatic attraction, the two can be easily adsorbed or combined together, providing the possibility or feasibility for the realization of immobilized enzymes.
[0210] Particle Charge Determination (PCD) measures the charge change during the Pul@CNF process:
[0211] like Fig.17 As shown in the figure, as Pul is gradually added to the CNF suspension, the originally clear CNF suspension gradually becomes turbid. This phenomenon is accompanied by a significant change in the charge state of the CNF solution, from the original positive charge state to the negative charge state. This phenomenon is attributed to the interaction between the quaternary ammonium groups carried by CNF and the carboxylic acid groups on the Pul molecules. Because the quaternary ammonium groups carried by CNF interact with the carboxylic acid groups on the Pul molecules. Under the action of electrostatic attraction, CNF and pullulanase are tightly bound, so that Pul can be stably fixed on the surface of CNF or in the network structure formed by CNF, thereby constructing a stable Pul@CNF.
[0212] Fig.18 is the standard curve of protein content. As the amount of Pul increases, its fixed amount also increases accordingly. However, when the enzyme addition reaches 120U / g, it is found that the immobilization sites on the CNF carrier have been saturated. This shows that the available sites on the carrier surface are limited. When the amount of Pul added exceeds this threshold, no more sites can be found for immobilization. As the amount of enzyme added increases, the proportion of free pullulanase in the solution gradually increases. This shows that when the amount of enzyme added reaches a certain value, the ability of CNF as an immobilization carrier will reach saturation and it will not be able to continue to adsorb more pullulanase. The research results show that CNF can effectively immobilize Pul, but its immobilization capacity is not without an upper limit.
[0213]
[0214]
[0215] Transmission electron microscopy (TEM) analysis and energy dispersive spectrometry (EDS) analysis:
[0216] like Fig.19As shown in Figure a, the CNF in Figure a shows a filamentous structure, and its surface is clean, and no significant black spots are observed. However, in Figure b, it can be clearly observed that there are obvious black dots attached to the surface of CNF. Further magnification shows that Figure c shows that these black dots are evenly distributed on CNF. It is speculated that these small black dots may be Pul particles that have successfully attached to CNF.
[0217] Because CNF carries a positive charge (with a quaternary ammonium group), it can electrostatically adsorb with the negatively charged pullulanase (carboxyl group). In addition, the high specific surface area and good biocompatibility of cellulose nanofibrils provide an ideal immobilization platform for CNF. These characteristics together contribute to the successful immobilization of pullulanase on cellulose nanofibrils. Through further elemental analysis, such as Fig. 20 Figure b is the superposition of the TEM image of Pul@CNF and the elemental scanning spectrum. After the N spectrum scan, the outline of CNF can be clearly seen. Figure c further confirms this, showing that the N element concentration on the outline is significantly higher than that in the surrounding area.
[0218] Scanning Electron Microscope (SEM) Analysis:
[0219] like Fig.21 As shown, it was found that the surface of cellulose nanofibrils without Pul attachment (Pul(0U)@CNF) was smooth and spotless. However, after adding Pul to the CNF surface, the SEM image showed that some obvious lumps appeared on the CNF surface. Further analysis showed that the number of these lumps increased with the increase in the amount of Pul. In particular, when the amount of Pul was 8U, these lumps were basically distributed on the entire surface of the cellulose nanofibrils. Based on the above observations, it can be concluded that Pul can be successfully attached to CNF. Moreover, within a certain range, as the amount of Pul increased, its attachment amount on CNF also increased accordingly. This finding not only confirms the feasibility of cellulose nanofibrils as a carrier for Pul immobilization, but also shows that there is a positive correlation between the amount of enzyme and the attachment amount within a certain range.
[0220] Confocal laser scanning microscopy (CLSM) analysis:
[0221] exist Fig. 22 In Figure a, some bright spots can be observed. The background color was adjusted and the Fig. 22 In Figure b, the spots fluoresce against the background and are attached to the filaments. Pul stained with FITC can appear as bright fluorescent spots against this background. This result directly confirms that Pul has been successfully fixed on the cellulose nanofibrils and intuitively shows the distribution of Pul on the cellulose nanofibrils.
[0222] Determination of the optimal pH value of enzyme reaction:
[0223] like Fig.23 As shown in the figure, with the increase of pH, the activity of immobilized enzyme and free enzyme showed a trend of first increasing and then decreasing. This shows that pH has a great influence on the enzyme. The optimal enzyme activity of free enzyme is at pH 5.5, and the optimal pH of immobilized enzyme is about 5. This shows that the immobilization process affects the optimal pH of the enzyme. Compared with the free enzyme, when pH ≤ 4 or ≥ 6, the immobilized enzyme has a stronger pH tolerance than the free enzyme. This may be because the conformation of the protein of pullulanase has changed after CNF immobilization, which improves the stability of the enzyme and its adaptability to specific substrates.
[0224] Determination of the optimal reaction temperature of enzyme:
[0225] like Fig.24 As shown in the figure, with the increase of temperature, the activity of immobilized enzyme and free enzyme showed a trend of first increasing and then decreasing. The maximum enzyme activity of both immobilized enzyme and free enzyme reached the maximum value at 60℃, indicating that immobilization did not affect the optimal reaction temperature of Pul. In the range of 30℃-50℃, the enzyme activities of immobilized enzyme and free enzyme were both increasing, and the enzyme activity of immobilized enzyme was greater than that of free enzyme. This may be because CNF can provide a stable environment, which is more conducive to enzyme reaction. In the range of 60℃-80℃, although the enzyme activities of immobilized enzyme and free enzyme were both decreasing, the enzyme activity of immobilized enzyme was higher than that of free enzyme. This may be because the secondary structure of Pul enzyme changed during the electrostatic adsorption of Pul to CNF, which enhanced the thermal stability of Pul and increased its enzyme activity.
[0226] Pul@CNF stability analysis:
[0227] like Fig.25 As shown in the figure, it was observed that the enzymatic activity of both the free enzyme and the immobilized enzyme showed a downward trend over time. After 3 days of reaction time, the enzymatic activity of the immobilized enzyme was still maintained at about 40% of the initial enzymatic activity, while the enzymatic activity of the free enzyme at the same time point was only 9.4%. This significant difference shows that the stability of the enzyme has been significantly improved after Pul was immobilized by CNF. The reason why the immobilized enzyme showed higher stability is that CNF provides a relatively stable microenvironment for the enzyme, which effectively slows down the influence of external environmental factors on the enzyme structure and activity.
[0228] Gel Permeation Chromatography coupled with Multi-Angle Light Scattering (GPC-MALS) analysis:
[0229] The data showed that the number average molecular weight (Mn) of the immobilized enzyme was relatively low, indicating that more small molecular weight substances were generated during the immobilization process. These small molecular weight substances may be short straight chains cut from the branch chains. In addition, the starch product treated with the immobilized enzyme has a lower weight average molecular weight (Mw), which may indicate that the content of high molecular weight substances in the product is reduced, further indicating that the immobilization treatment promotes the enzymatic hydrolysis of more branch chains. At the same time, the polymerization degree dispersity index (PD value) of the two samples is similar, showing that the polymerization degree dispersity of the two samples is relatively good. ( Fig.26 It can be seen that the overall dispersibility of starch is good). This result shows that the immobilization technology improves the activity of the enzyme and can promote the further enzymatic hydrolysis of the branched chain by Pul.
[0230] GPC test results data table
[0231] project Immobilized enzyme Free enzyme Mn (number average molecular weight) 226,160 267,318 Mw (weight average molecular weight) 1,630,847 1,874,907 PD (Polymerization Dispersity) 7.21103 7.01377
[0232] X-ray diffraction (XRD) pattern analysis:
[0233] In the process of data visualization, choosing the appropriate chart type is crucial to effectively convey information. In Chapter 23, a Y-offset stacked line chart was used to highlight the cumulative changes of different categories of data with another variable. However, when it is necessary to observe the trend of a specific data point in more detail, an XY line chart is selected, such as Fig. 27 As shown in the figure, the enzyme stability of the immobilized enzyme is improved compared with the free enzyme, but there is no obvious difference in the XRD patterns of Pul@CNF-StF and Pul / CNF-StF. This shows that the stability of the immobilized enzyme is improved, but the crystal form of the starch film is not changed.
[0234] The XRD spectrum data was processed by Jeda6.5 software and the crystallinity of the starch film was calculated. The crystallinity of Pul / CNF-StF was 22.78% and that of Pul@CNF-StF was 24.20%. The crystallinity of Pul@CNF-StF was higher than that of Pul / CNF-StF, indicating that the stability of the immobilized enzyme was improved, which improved the enzyme efficiency, and more straight-chain starch could be hydrolyzed, forming a spiral, orderly arranged when cooled, increasing the short-range ordered structure, and improving the mechanical properties.
[0235] Fourier transform attenuated total reflectance infrared spectroscopy (ATR-FTIR) analysis:
[0236] pass Fig.28 a It can be seen that no new chemical bonds are generated before and after Pul@CNF-StF and Pul / CNF-StF, which indicates that the fixed Pul does not affect the chemistry of starch.
[0237] The ratio of 1046cm-1 / 1022cm-1 of the composite film prepared by enzymatic hydrolysis of starch by fixed Pul (Pul@CNF-StF) is higher than that of the film prepared by free enzyme-treated starch (Pul / CNF-StF), which indicates that the enzymatic hydrolysis of starch by Pul@CNF produces more directly connected starch, and produces a spiral structure and orderly arrangement when cooled, and the short-range order increases.
[0238] The ratio of the absorbance at 1046cm-1 / 1022cm-1 after deconvolution of the infrared spectrum of starch film
[0239] sample 1046cm-1 / 1022cm-1 (short-range order) Pul / CNF-StF 0.560±0.003 Pul@CNF-StF 0.581±0.004
[0240] Scanning electron microscope (SEM) observation:
[0241] from Fig.29 The surface of the starch film treated with Pul immobilized enzyme (Pul@CNF-StF) and the starch composite film treated with free enzyme (Pul@CNF-StF) are relatively smooth, and the cross section is relatively flat, which shows that the treatment of starch with Pul after CNF immobilization does not affect the compatibility between starch molecules.
[0242] Mechanical properties determination:
[0243] As shown in Figure 30, the tensile strength of the starch film (Pul@CNF-StF) prepared by enzymatic hydrolysis after immobilization is 9.29MPa, which is greater than the tensile strength of the starch film (Pul / CNF-StF) prepared by enzymatic hydrolysis of starch with free enzymes (8.74MPa). Because the enzyme is immobilized, the stability of the enzyme is enhanced, and the enzymatic hydrolysis of starch produces more amylose. The short-range order of Pul@CNF-StF increases, and the molecular arrangement is more regular, so that the starch film can better disperse the stress when subjected to external force, thereby improving the mechanical properties of starch.
[0244] Thermogravimetric analysis:
[0245] like Fig.31 As shown in a, from the TG curve, the overall weight loss trend of the starch film treated with immobilized enzyme (Pul@CNF-StF) and the starch film treated with free enzyme (Pul / CNF-StF) is slightly different. All films show a three-step thermal degradation stage. 290℃-600℃ is the change of starch degradation, and the weight loss of Pul@CNF-StF is slightly lower than that of Pul / CNF-StF. Fig.10 In the thermogravimetric curves of different CNF addition amounts, different amounts of CNF were added to the starch film, and the residue increased because hydrogen bonds and other interactions occurred between CNF and amylose, thereby enhancing the interfacial bonding between the two and generating a more stable substance. The immobilized enzyme can hydrolyze more amylose, which can interact with CNF to form a more stable substance.
[0246] In order to fully understand the thermal behavior of the different composite films studied, the first-order derivative TGA curves were calculated, and Figure b was obtained. From 290°C to 600°C, the maximum degradation temperatures of Pul@CNF-StF and Pul / CNF-StF were both at 314°C. Increasing the amount of Pul on the starch film did not change the maximum degradation temperature, indicating that the immobilized enzyme treatment did not change the thermal stability of the starch film.
[0247] The present invention and its embodiments are described above, and such description is not restrictive. What is shown in the full text is only one of the embodiments of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.
Claims
1. A method for directionally regulating the content of straight chain in starch and improving the performance of starch film, characterized in that: The following steps are involved: S1. Starch modification: The starch is dissolved in an ionic liquid at a temperature of 75-80°C, and then dried in an ozone environment to form an absolutely dry starch with a rough and bumpy surface; S2. Preparation of pullulanase immobilized on cellulose nanofibrils: Weigh 2-15g of absolute dry starch as a substrate, add 1.0%-10% CNF relative to the mass of starch, the dosage is 1U-10U per gram of absolute dry starch, add phosphate buffer, adjust the pH value of the mixture to 6, add 4U of Pul protein per gram of absolute dry starch, and add pullulan, and shake the mixture in a constant temperature air bath to complete the immobilization of pullulanase on cellulose nanofibrils to obtain Pul@CNF complex; S3. Preparation of active substances: Add polyphenols to the Pul@CNF composite and mix well, add konjac glucomannan in portions, and mix in a pressure cooker at a pressure of 200-230 MPa and a temperature of 35-45°C for 15-18 min; S4, Cellulose nanofibril immobilized pullulanase system enzymatically hydrolyzes starch into film: Take 2-8g of absolute dry starch and place it in a 250ml three-necked flask. Then add 20-80ml of distilled water and place it in a 38°C water bath. Slowly stir to disperse the starch. After fully stirring for 5 minutes, add Pul@CNF in step S3, add water to 100ml, continue stirring for 10 minutes, and heat to 95°C at a rate of 1°C / min. After reaching this temperature, add 20-80% of the mass of absolute dry starch to the solution. Plasticizer, and keep warm for 30 minutes. After stirring, remove bubbles from the obtained starch solution, spread it evenly on an acrylic plate by casting, and dry it in an oven at 50°C for 8 hours. After drying, a starch film is obtained.
2. The method for directionally regulating the content of straight chain in starch and improving the performance of starch film according to claim 1, characterized in that: The drying time in the ozone environment is 8-10 minutes.
3. The method for directionally regulating the content of straight chain in starch and improving the performance of starch film according to claim 1, characterized in that: The cellulose nanofibrils are one or any combination of anionic, cationic, and neutral cellulose nanofibrils.
4. The method for directionally regulating the content of straight chain in starch and improving the performance of starch film according to claim 1, characterized in that: The pH value of the phosphate buffer is 4-7.
5. The method for directionally regulating the content of straight chain in starch and improving the performance of starch film according to claim 1, characterized in that: The starch is one or any combination of corn starch, tapioca starch, potato starch and sweet potato starch.
6. The method for directionally regulating the content of straight chain in starch and improving the performance of starch film according to claim 1, characterized in that: The cellulose nanofibrils are one or any combination of anionic, cationic, and neutral cellulose nanocrystals.
7. The method for directionally regulating the content of straight chain in starch and improving the performance of starch film according to claim 6, characterized in that: The neutral cellulose nanocrystal has a length of 100nm-5000nm, a diameter of 1-20nm, and a solid content of 0.01%-5%.
8. The method for directionally regulating the content of straight chain in starch and improving the performance of starch film according to claim 1, characterized in that: The plasticizer is one or any combination of glycerol, urea, ethylene glycol, polyethylene glycol, propylene glycol, sorbitol, and ethanolamine.
9. The method for directionally regulating the content of straight chain in starch and improving the performance of starch film according to claim 1, characterized in that: The mixture was placed in a constant temperature air bath shaker at 30°C and incubated at 100-300 rpm for 1-3 h.